Exploring disconnected discourses about Patient and Public Involvement and Volunteer Involvement in English health and social care. (1st December 2020) - Grotz, Jurgen; Birt, Linda; Edwards, Heather; Locke, Michael; Poland, Fiona
Abstract: Background: Patient and public involvement (PPI) in health and social care policy, service decision‐making and research are presented as good practice in England. Yet the explicit rationale for PPI and how it is positioned within the literature, policy and practice remain confused, in particular, in relation to Volunteer Involvement (VI). In health and social care, PPI and VI are managed and valued as conceptually distinct, yet the discourses in their policy and practice documents treat them as closely related in fundamental ways. Objective: Compare and critically evaluate discourses framing PPI and VI within English health and social care. Design: A critical discourse approach was used to explore the accounts of PPI and VI in policy. These accounts were then compared and contrasted with personal accounts of volunteering in health and social care settings. Results: Twenty documents from key national health and social care bodies were discursively examined in terms of their framing PPI and VI. A narrative disconnect between the two was repeatedly confirmed. This finding contrasted with an analysis of personal accounts of VI which displayed VI as a form of PPI. Conclusion: There is a disconnect between language, narratives and practice in PPI and in VI which may have direct consequences for policy and practice. Recognising and managing it can offer innovative ways of enabling volunteers to be involved across health and social care settings, ensuring the experiential value added by volunteers' service contributions, to be recognised so that their democratic participation may be seen to shape services.